Autentikasi Elektronik dalam Kitab Undang-Undang Hukum Acara Pidana Baru: Studi Komparatif Amerika Serikat : - Shera Rendra; Emmilia Rusdiana (Unram Law Review, 2026)
This study examines the concept of authentication of electronic evidence within the Indonesian criminal evidentiary system under Law Number 20 of 2025 concerning the Criminal Procedure Code (Kitab Undang-Undang Hukum Acara Pidana / KUHAP) and analyses the urgency of regulating a self-authentication mechanism through hash values by conducting a comparative study with the United States Federal Rules of Evidence (FRE). The research employs a normative legal research method, drawing on statutory and comparative law. The findings demonstrate that although the new KUHAP has recognised electronic evidence as admissible, it does not specifically regulate technical authentication procedures. In contrast, Rules 902(13)–(14) of the Federal Rules of Evidence have established an efficient, standardised self-authentication mechanism based on hash values, which may be adopted and adapted within the Indonesian legal system.